Early kinematic history of the Goban Spur rifted margin derived from a new model of continental breakup and sea floor spreading initiation - Healy, David; Kusznir, N. (Geological Society of London, 2007)
Deformation of continental lithosphere leading to breakup and the initiation of seafloor spreading can be described in terms of an upwelling divergent flow field within the continental lithosphere and asthenosphere. A new model (SfMargin) of rifted continental margin formation using this upwelling divergent flow field has been developed that successfully predicts lithosphere depth-dependent stretching and mantle exhumation at rifted margins. The kinematics of this flow field has important consequences for the bathymetric (subsidence) and thermal history of continental margin lithosphere. We apply the new model to a profile through the Goban Spur on the eastern Atlantic continental margin. Forward modelling yields parameter values describing the kinematics of the flow field leading to continental breakup and sea-floor spreading initiation that are consistent with the known amagmatic history of this margin. We employ a grid search method to systematically explore model parameter space and provide an assessment of the sensitivity of the model to the kinematic flow field parameter values. The preferred forward model parameters coincide with low values of misfit with respect to observed present-day bathymetry and free air gravity anomalies. Our results reveal the early kinematic history of the Goban Spur margin as characterized by a ratio of upwelling rate to half-spreading rate of unity, consistent with that expected for the initiation of sea-floor spreading at a non-volcanic rifted margin and only a modest amount of prebreakup lithospheric stretching (b ¼ 1.5). These results conform with recent observations of depth-dependent stretching and serpentinized mantle exhumation at this amagmatic rifted continental margin.